A primer on studying effects of relationship duration in dyadic research: Contrasting cross-sectional and longitudinal approaches. (June 2022) - Brauer, Kay; Sendatzki, Rebekka; Proyer, René T.
There has been increasing interest in the analysis of dyadic data. While there is ongoing progress in the development of statistically fine-grained methods to model complex dyadic data, many studies examine relationship duration in dyads using cross-sectional data (e.g., when testing the effects of acquaintanceship on the accuracy of personality judgments). We discuss the theoretical and methodological implications of analyzing and interpreting time-based variables in dyadic research on basis of the cross-sectional and longitudinal design approaches. We give examples from the literature on romantic relationships and interpersonal perception. Finally, we derive recommendations on addressing questions of time-based indexes in dyadic research and discuss advantages and disadvantages of each approach.